Pengaruh Digitalisasi dan Solvabilitas Terhadap Nilai Perusahaan dan Profitabilitas pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024 - Annisa, Safira Nur; Amalia, Naili (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
Firm value and profitability play a crucial role as key indicators of an entity's financial performance. The implementation of digitalization has the potential to enhance operational efficiency and competitive advantage, whereas solvency reflects a firm's capability to fulfill long-term debt obligations. This study examines the impact of digitalization and solvency on firm value and profitability among manufacturing issuers listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Employing a quantitative approach, secondary data were gathered from financial statements and annual reports obtained from the official IDX website as well as the respective corporate websites. Based on purposive sampling criteria, a sample of 68 companies was selected, yielding a total of 204 observations. Data were analyzed using panel data regression techniques via EViews 13, incorporating model selection tests, classical assumption tests, and statistical tests (t-test, F-test, and coefficient of determination). The results indicate that digitalization has a positive but statistically insignificant effect on firm value, as well as a positive but statistically insignificant effect on profitability. Solvency exhibits a negative but statistically insignificant effect on firm value, whereas it exerts a negative and statistically significant effect on profitability. Furthermore, the F-test results reveal that digitalization and solvency simultaneously do not significantly influence firm value, yet they exert a significant combined effect on profitability. Finally, the coefficient of determination demonstrates that the firm value model possesses a very low capacity to explain variations in firm value, whereas the profitability model exhibits a superior explanatory power in capturing variations in profitability.